2024
DOI: 10.1002/mus.28035
|View full text |Cite
|
Sign up to set email alerts
|

Segmental motor neuron dysfunction in amyotrophic lateral sclerosis: Insights from H reflex paradigms

José Castro,
Miguel Oliveira Santos,
Michael Swash
et al.

Abstract: Introduction/AimsIn amyotrophic lateral sclerosis (ALS), the role of spinal interneurons in ALS is underrecognized. We aimed to investigate pre‐ and post‐synaptic modulation of spinal motor neuron excitability by studying the H reflex, to understand spinal interneuron function in ALS.MethodsWe evaluated the soleus H reflex, and three different modulation paradigms, to study segmental spinal inhibitory mechanisms. Homonymous recurrent inhibition (H'RI) was assessed using the paired H reflex technique. Presynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…In accordance with the results obtained in animal models, spinal inhibition is reduced in human patients as the disease progresses. Observations suggested that recurrent inhibition involving Renshaw cells (see above) is decreased in patients showing spinal symptoms (Howells et al, 2020 ; Ozyurt et al, 2020 ; Sangari et al, 2022 ; Castro et al, 2024 ). Interestingly, an increase in recurrent inhibition was observed in the early phase of the disease in one of these studies, supporting the hypothesis of an initial compensatory mechanism preventing MN decline (Sangari et al, 2022 ).…”
Section: Alterations Of Spinal Inhibitory Pre-motor Insmentioning
confidence: 99%
“…In accordance with the results obtained in animal models, spinal inhibition is reduced in human patients as the disease progresses. Observations suggested that recurrent inhibition involving Renshaw cells (see above) is decreased in patients showing spinal symptoms (Howells et al, 2020 ; Ozyurt et al, 2020 ; Sangari et al, 2022 ; Castro et al, 2024 ). Interestingly, an increase in recurrent inhibition was observed in the early phase of the disease in one of these studies, supporting the hypothesis of an initial compensatory mechanism preventing MN decline (Sangari et al, 2022 ).…”
Section: Alterations Of Spinal Inhibitory Pre-motor Insmentioning
confidence: 99%